Numerical Modelling of NACA 0015 Airfoil Under Erosion Condition - Billad, Rayhan Fariansyah; Julian, James; Wahyuni, Fitri; Iskandar, Waridho (Jurnal Rekayasa Mesin, 2024)
Airfoils that experience erosion with varying Reynolds numbers were studied using numerical methods to determine the effect on the performance of the NACA 0015 airfoil. A Computational Fluid Dynamics (CFD) approach has been used to this research. Reynolds Averaged Navier-Stokes (RANS) was used as the governing equation used in this research. The turbulence model used in this research was k-epsilon model. The Reynolds numbers used are 1.6 Ã— 10â¶, 2 Ã— 10â¶, and 2.5 Ã— 10â¶. This research proves that erosion can reduce the Cl value and increase the Cd value on the NACA 0015 airfoil. Increasing the Reynolds number can also reduce the average Cl value and increase the average Cd value. The decrease in the average value of Cl is 6.561%, 9.392%, and 9.803%, respectively, at Reynolds numbers 1.6 Ã— 10â¶, 2 Ã— 10â¶, and 2.5 Ã— 10â¶. Then, the average Cd value increase is 1.120%, 1.301%, and 1.396%, respectively, at Reynolds numbers 1.6 Ã— 10â¶, 2 Ã— 10â¶, and 2.5 Ã— 10â¶. The contour visualization shows that the airfoil erosion has a pressure contour that increases in the upper chamber and decreases in the lower chamber. This phenomenon also occurs as the Reynolds number increases so that it can reduce the lifting force of the NACA 0015 airfoil. The flow velocity and streamlined contours also show greater circulating flow on the erosion airfoil, which can accelerate the 1 ° AoA stall on the erosion airfoil. The circulating flow also becomes larger as the Reynolds number of the airfoil increases.